Reinforcing the Comprehension of Islamic Education Through the Kajian Ahad Pagi at the Mosque - Aziz, Arinal; Faridi, Faridi; Sunarto, Sunarto (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the process of understanding Islamic education through the Sunday Morning Study (Kajian Ahad Pagi) at At-Taqwa Muhammadiyah Mosque in Blitar City, as well as its impact on the lives of the congregation. The research adopts a qualitative descriptive approach and utilizes a case study design. Data collection techniques include observation, interviews, and documentation. Data were analyzed using the Miles, Huberman, and Saldana model, which involves data reduction, data presentation, and conclusion drawing. The findings reveal that the process of reinforcing religious understanding is carried out through the delivery of materials relevant to daily life using lecture and discussion methods. These methods enable the congregation not only to receive information but also to internalize Islamic values in their everyday lives. The impact of this study is evident in changes in the congregation's behavior, including improved religious understanding, increased patience, heightened social awareness, and active participation in religious and social activities within the community. This study affirms that community-based Islamic education, particularly through religious studies held in mosques, is highly effective in shaping a pious and morally upright society. These findings may serve as a valuable reference for developing non-formal Islamic education programs in other mosques.